2022
DOI: 10.1177/00223433221075191
|View full text |Cite
|
Sign up to set email alerts
|

Anger and support for retribution in Mexico’s drug war

Abstract: How does exposure to criminal violence shape attitudes towards justice and the rule of law? Citizens care about crime prevention and procedural legality, yet they also value punishing perpetrators for the harm they have done. We argue that anger induced by exposure to criminal violence increases the demand for retribution and harsh punishments, even at the expense of the rule of law. We test this theory using one observational and two experimental studies from an original survey of 1,200 individuals in Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 52 publications
2
33
1
1
Order By: Relevance
“…The dependent variable not only captures high-risk mobilization, but it does so across four years in time. As such, my data go beyond studies that measure attitudes toward vigilantism (Zizumbo-Colunga 2017; García-Ponce et al 2021) or attitudes toward the use of violence (Cruz and Kloppe-Santamaría 2019). My dependent variable also offers more variation than either Phillips’s (2017) or Osorio et al’s (2019) dummy variable measuring whether at least one vigilante group existed in a Mexican municipality in just one year.…”
Section: Data Sources Research Methods and Operationalizationmentioning
confidence: 92%
“…The dependent variable not only captures high-risk mobilization, but it does so across four years in time. As such, my data go beyond studies that measure attitudes toward vigilantism (Zizumbo-Colunga 2017; García-Ponce et al 2021) or attitudes toward the use of violence (Cruz and Kloppe-Santamaría 2019). My dependent variable also offers more variation than either Phillips’s (2017) or Osorio et al’s (2019) dummy variable measuring whether at least one vigilante group existed in a Mexican municipality in just one year.…”
Section: Data Sources Research Methods and Operationalizationmentioning
confidence: 92%
“…These incidents suggest that vigilante violence continues to be inflicted on perceived offenders, whether Muslim or non-Muslim, as an emotional reaction to (perceived) crimes. According to the Center for Research and Security Studies (2014) and Hashim (2020), since 1990, approximately 52–77 alleged blasphemers have been killed by angry vigilantes. This indicates that people may be emotionally attached to religion and that whenever they construe encroachment on their religious values, they vent their anger by punishing the alleged offenders themselves.…”
Section: Vigilante Violence In Pakistan: a Contextual Overviewmentioning
confidence: 99%
“…Adzimah-Alade et al (2020) analyzed 172 media reports from 2000–2018 in Ghana and found that theft and robbery were the main reasons (117/172) for which offenders were attacked and lynched by vigilantes. Likewise, the Center for Research and Security Studies (2014) and Hashim (2020) have reported that since 1990, approximately 52–77 people have been killed extrajudicially in Pakistan by vigilantes owing to reports of the offenders making blasphemous statements. Thus, the researcher created vignette scenarios regarding such offenses (for precedents on the use of situation-based vignettes regarding such offenses, see Haas et al, 2012, 2014; Nivette, 2016).…”
Section: Dependent Variablementioning
confidence: 99%
“…The psychological impact of war, terror, and LICs on civilians and societies has been widely studied, dealing with the vulnerability and resiliency of communities and individuals who facing terrorism and war [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Researchers conducted in many countries that indicate that armed conflicts and terror attacks have a significant impact on emotions, fears, stress, and posttraumatic stress disorder [ 7 , 12 , 13 , 19 , 20 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%